Spatio-temporal variation in the phytobenthos and phytoplankton community structure and composition of particulate matter along a river-estuary continuum assessed using microscopic and stable isotope analyses - Dalu, Tatenda (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Phytoplankton and phytobenthos communities play an important role in lotic systems as primary producers providing essential biomolecules to higher trophic oganisms and are important indicators for environmental or ecological change. In this thesis, field studies (observational and experimental) along a river"“estuary continuum were conducted to assess the spatio-temporal variation and development of phytobenthos and phytoplankton communities using a combination of stable isotope and community analyses in a temperate southern African system across four study periods: September (early spring) and November/December (late spring) 2012, and February (summer) and May/June (winter) 2013. Additionally, the sources and composition of the particulate organic matter were also analysed using stable isotope (Î´15N and Î´13C) analysis. The effects of substrate type and flood occurrence were assessed through experimental studies at an up- and downstream site of the river after a major flood event that occurred between October and November 2012. Common household tiles were used as artificial substrates to study the development/succession of phytobenthos communities after the flood disturbance. Distinct diatom communities were observed between upstream and downstream sites and at each site, community structure changed with time indicating succession. In addition to recording diatom characteristics on three natural substrates, namely; macrophytes, rocks and sediment, artificial substrates observations were also made on three different types of artificial substrates, namely; brick, brown clay and grey clay tiles. The natural (species richness 78) and artificial substrates (sp. richness 93) had different communities with the latter having greater species richness. Common phytobenthos taxa were not restricted to a single substrate but preference was generally high for the artificial substrates, especially brown tiles (mean sp. richness 47). Results of the redundancy analysis (RDA) analysis indicated that ammonium, conductivity, total dissolved solids, salinity, pH, oxygen reduction potential, phosphate and water depth were the major determinants of the phytobenthos composition at the two sites. The spatio"“temporal variation of phytoplankton and phytobenthos communities and allochthonous organic matter along the river"“estuary continuum was assessed at 8 sites using a combination of community and stable isotope analyses. A total of 178 species belonging to 78 genera were recorded with diatoms being predominant, accounting for 81.9 % of the total abundance. The total chl-a concentration along the river-estuary continuum increased from spring to a high in summer before decreasing to a low in winter. Periphyton communities were observed to be significantly different across sites (p < 0.05) in terms of species richness, abundances and isotopically The high periphytic Î´15N values (range 7.9"“15.2 "°) recorded at the downstream sites compared to the pristine upstream sites (Î´15N values range 4"“7 "°) suggest nutrient enrichment most likely derived from anthropogenic sources. Overall, our results reveal general patterns of periphyton communities and stable isotopes and provide improved information in the use of periphyton Î´15N as an excellent indicator of anthropogenic nitrogen pollution. Ecologists are interested in the factors that control, and the variability in, the contributions of different sources to mixed organic materials traveling through lotic systems. We hypothesized that the source matter fuelling mixed organic pools in a river-estuary continuum varies over space and time, with the upper reaches of a system characterized by allochthonous-dominated material and autochthonous contributions becoming more important in the lower reaches. Samples of the mixed organic pools and allochthonous and autochthonous source materials were collected during the four study periods. The C:N ratios of suspended particulate matter (SPM) collected during summer and winter indicated that the lower reaches of the system had similar organic matter contributions from the freshwater and terrestrial sources. Stable isotope analysis in R revealed that the contributions of autochthonous organic matter were high in SPM along the entire continuum, and aquatic macrophytes were significant contributors to SPM specifically in the upper reaches. The terrestrial leaves made major contributions to the SPM in the middle regions of the system (i.e. downstream sites of the river, particularly in early and late spring). Bulk detritus had large allochthonous matter components in the lower reaches (estuary), and the contributions of aquatic macrophytes and benthic algae to bulk detritus were high (> 50 %) in the upper to middle reaches (river), but low (< 20 %) in the lower reaches (estuary). The current investigation represents the first attempt to assess the validity of the River Continuum Concept (RCC) in a southern African temperate river. The phytoplankton and phytobenthos communities, and chl-a concentration followed a trend similar to that proposed for the river continuum concept (RCC). The middle reaches based on the phytobenthos or phytoplankton communities and chl-a concentrations which were employed as proxies for primary production, were the most productive, while the upper reaches were the least primary productive. The evaluation of organic matter contributions to the SPM and detritus along the river"“estuary continuum provided a baseline assessment of the nature and sources of potential food for consumers inhabiting different locations during different times of the year. Incorporating such spatio-temporal variations in SPM and detritus into food web studies will improve our understanding of the flow of carbon through aquatic systems.
Keywords: Uncatalogued